Thesis and Research Writing in English by Indonesian Higher Degree Students Studying Overseas - Lloyd Holliday (TEFLIN, 2001)
Indonesian Research Degree Student studying overseas in Australian Universities, ie. those undertaking a PhD, EdD, or Master Degree by Coursework and Minor Thesis, have exactly the same problems in thesis writing as local Australian students. They may have minor problems of language in writing in English as a result of transfer from Bahasa Indonesia. But the major problems of all first time research degree students is learning how to become researchers and how to present their research in a discourse format as a thesis or dissertation that has become the assepted norm internationally. This paper firstly examines some of the common surface written language problems of Indonesian Higher Degree Students. This data id drawn from an analysis of actual drafts of these written over the last ten years by a range of Indonesian students. Secondly, the paper discusses the nature of developing as a researcher and the associated problems of how this influences the presentation of research. And thirdly, the paper reflects on ways in which the process of learning of think and write as a researcher can be facilitated.